PENGARUH PENGGUNAAN MEDIA BERBASIS ASSEMBLR EDU TERHADAP HASIL BELAJAR SISWA PADA MATERI IPAS KELAS IV SD NEGERI 195 PALEMBANG - Nia Dilpiani; Murjainah; Maharani Oktavia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The formulation of the problem in this study "is there an effect of using AssemblrEdu-based media on student learning outcomes in the science material of gradeIV of State Elementary School 195 Palembang. The purpose of this study was todetermine the effect of using Assemblr Edu media on student learning outcomes inthe science material of State Elementary School 195 Palembang. The researchmethod used quantitative research true experimental design with posttest onlycontrol design. The population of this study was grade IV of State ElementarySchool 195 Palembang with research samples, namely class IV. A as theexperimental class and class IV. B as the control class. The results of thenormality test with a sig. level ≥ 0.05, the data in the experimental class obtained aresult of 0.151 ≥ 0.05 and the control class obtained a result of 0.131 ≥ 0.05 withan average value of the experimental class of 78.53 while the average value of thecontrol class was 65.56. Based on the results of the independent sample t-testassisted by the SPSS version 26 application, sig. (2-tailed) of 0.000 < 0.025 wasobtained. Based on the decision criteria, Ho is rejected and Ha is accepted, so it isproven that the use of Assemblr Edu-based media has an effect on studentlearning outcomes.